2016
DOI: 10.3928/01477447-20160301-01
|View full text |Cite
|
Sign up to set email alerts
|

To Beard or Not to Beard? Bacterial Shedding Among Surgeons

Abstract: Beards in the operating room are controversial because of their potential to retain and transmit pathogenic organisms. Many bearded orthopedic surgeons choose to wear nonsterile hoods in addition to surgical masks to decrease contamination of the operative field. The goal of this study was to determine whether nonsterile surgical hoods reduce the risk of bacterial shedding posed by beards. Bearded (n=10) and clean-shaven (n=10) subjects completed 3 sets of standardized facial motions, each lasting 90 seconds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 13 publications
1
27
1
Order By: Relevance
“…The positive association we report here could be interpreted as support for parasite resistance handicap hypotheses [ 69 ], as facial hair has the potential to harbor disease carrying ectoparasites, that may have impact on male survivability ancestrally [ 34 36 ], so that only high quality males could maintain beards. However, evidence from medical studies that beards harbor bacteria is mixed [ 50 , 70 , 71 ] and we found no causative effect of priming pathogens on preferences for beards. The negative association between preferences for beards and self-reported sexual disgust might reflect preferences for cues of masculine conservatism, as facial hair is associated with masculinity and dominance [ 72 76 ], political conservatism [ 77 ] and the endorsement of gender typical roles in heterosexual relationship [ 78 , 79 ].…”
Section: Discussioncontrasting
confidence: 60%
“…The positive association we report here could be interpreted as support for parasite resistance handicap hypotheses [ 69 ], as facial hair has the potential to harbor disease carrying ectoparasites, that may have impact on male survivability ancestrally [ 34 36 ], so that only high quality males could maintain beards. However, evidence from medical studies that beards harbor bacteria is mixed [ 50 , 70 , 71 ] and we found no causative effect of priming pathogens on preferences for beards. The negative association between preferences for beards and self-reported sexual disgust might reflect preferences for cues of masculine conservatism, as facial hair is associated with masculinity and dominance [ 72 76 ], political conservatism [ 77 ] and the endorsement of gender typical roles in heterosexual relationship [ 78 , 79 ].…”
Section: Discussioncontrasting
confidence: 60%
“…There was no significant difference in the number of bacteria shed by the surgeons wearing masks and surgical hoods and the surgeons wearing masks alone; however, the unmasked surgeons shed a significantly higher number of colony‐forming units than the masked surgeons or surgeons wearing masks and hoods. The bearded surgeons did not shed more bacteria compared with the clean‐shaven surgeons in any of the tests …”
Section: Covering Beards In the Perioperative Environmentmentioning
confidence: 89%
“…Facial hair has always been a contentious issue in infection prevention. Perry et al conducted research to investigate whether clinicians' facial hair may contribute to increased bacterial shedding and subsequent SSIs 15 . The results showed a statistically significant difference with bacterial shedding from bearded men being lower in the face mask cohort than those without surgical masks (p < 0.02) 15 .…”
Section: Surgical Masks and Facial Hairmentioning
confidence: 99%